Port (Bandar), Heritage Landscape of a Territory - Seyed Amir Mansouri (منظر, 2022)
The beach of the city, known as Port is called Bandar in the Persian language. There are two narrations attributed to it in this language: The first one, with transliteration of Bondar, in which kind of stuff is placed (according to Dehkhoda Lexicon), and second composed of ‘Band’ (enclosed), and ‘Dar ‘(door) means a pond-like enclosed area with a gate. The word "Bandar" entered the Arabic language with the plural form of "Banader" which means ports. In Hindi and Indonesian, there is a similar word called Bandargah, which points to the harbor. There are several ports around the world whose names are composed of Bandar. Coastal life is highly influenced by the sea. For coastal inhabitants, the sea is the origin of life and meaning. For those who live by the sea, the landscape of the sea is the reason for the existence of the city and motivation for its survival. The living connection with the sea is the secret of this landscape. The emerging point of these two entities is the borderline between the city and the sea; however, their relationship is expanded to all aspects of life, including: culture, architecture, food, occupation, religion, economy, and society. If living condition depends on the presence of the sea, it is not far-fetched to be the source of other inspirations as well. The sign and symbols, and the representation of human interaction with the nature of the sea appear at the border of their connection, which is the port, and its landscape is the representative of this connection; The port cities and villages have created the compound and complicated emerged relations at this borderline, which according to the local people all these manifestations together are all called ports. On the other hand, with the expansion of urbanization and the growth of port trade, together with the facility services, the part of the whole port which was allocated to the warehouses and transportation facilities, abruptly became the owner of this historical and cultural concept of human civilization. The growth of bureaucracy and the power of central government caused the formation of the 'Ports and Shipping Organization' in the country, which by ignoring the public rights and the cultural heritage of the ports, just relying on the organizational interests and taking advantage of the power, controlled the vital edge of this coastline, and dispossessed the citizens of this unique inspiration source and the reason behind the establishment of their city. Although, the port is a representative of the past and future interactions with the sea, not just a commercial task, the 'Ports and Maritime Organization of Iran' established a strong barrier around its entity to commit to the law, which was not according to the public advantages, but just to meet the partial interests of some groups; it was in a situation where this barrier affected the contact area used to be presented between the city and the sea. To experience the sea, people had to exit the city limits. The extent of damaging this borderline gradually increased, as the sea area was also occupied. Pushing back the sea has become so popular as a creative method under the title of 'land fill' or 'land reclamation'. The authorities tried to manage it extensively and make a 'shoreline retreat' by attracting more funds and moving landward, to get new areas for their activity. This procedure is also imitated by the municipality of port cities in moving seashores. At the far end of the beach, a high wall is built, and by filling the space behind it, a platform overlooking the sea is constructed to consider it as a land area added to the city land. These measures adversely affect people's feeling attached to the sea when they used to experience walking on the beach sands to let the water waves touch their feet. The actions pull people back from 'the sea' area to the 'offshore'; it looks like the authorities are unaware of the damage to the landscape, which used to be the source of inspiration for the residents. The protection of marine civilization is highly dependent on the long-term interaction between humans and the sea. It is not appropriate to extensively occupy the environment, whether willingly or unwillingly, just by exploiting engineering methods. The journal cover image shows 'Chābahār Port', which represents the active nature of the port, its access way on the coastal edge, and the vast areas dedicated to the port dock. All these actions are interventions in the historical and natural edge of the contact area, between the city and the sea, like a barrier prevents the continuity of the citizens' perception of their land. The material achievements arising from invading this precious gem in exchange for losing opportunities for expanding civilization and continuity of identity are so insignificant that they seem negligible in the macro economy of society.